To assess the adherence to antiretroviral therapy among HIV positive patients attending ART centres in Haryana and its effect on their quality of life - Singh, Arundeep; Mittal, Anshu; Kaur, Vishavdeep (Indian Journal of Community Health, 2021)
Background: Acquired immune deficiency syndrome (AIDS) is now considered as a manageable chronic illness with the availability of ART. A high level of adherence (>95%) is required for antiretroviral therapy to be effective. It is a syndrome that builds a vacuum in a person affecting his/her quality of life (QOL) as a whole. Aim& Objective: The aim of our study was to determine adherence and its effect on their quality of life among HIV/AIDS patients attending FIART (Facility Integrated Anti-retroviral therapy) clinic. Materials and Methods: Using a cross-sectional study design, 257 HIV positive patients receiving antiretroviral therapy at Facility integrated anti-retroviral therapy centre Ambala Haryana. QOL of patients taking ART was assessed using WHO-QOL-BREF questionnaire. Results: Of 257 participants, 88.3% were found to be adherent, adherent to ART therapy and ambulatory had better QOL (p < 0.05) than their counterparts from other socio-clinical strata. Mean scores of physical (70.89±7.384), psychological (47.37±9.174), social (51.97±11.119) & environmental domains (52.33±9.081), were having highest in patients those who were adherent (adherence rate >95%) to ART therapy. Conclusion: Adherence to antiretroviral therapy in Haryana India is suboptimal. Intensive adherence counselling should be provided to all patients before initiation of antiretroviral therapy and on every visit to FIART centre.